DETERMINAN CURAHAN JAM KERJA PEREMPUAN KEPALA RUMAH TANGGA DI JAWA TIMUR - Yusuf Amri; Unggul Widyanarko (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2023)
East Java has the highest percentage of female heads of household workers in Indonesia. This percentage has increased since 2011, along with the increase in divorce rates and the shift in the role of women from the domestic sector to the labor market. The objectives are to explain female head-of-household workers' social and demographic characteristics and analyze the factors that influence their total work hours. The duration of working hours is the dependent variable. Age, marital status, education, occupational status, sector of occupation, and number of household members as independent variables. Data were obtained from the 2017 National Socio-Economic Survey (Susenas) activities, with 7652 respondents. This research method uses descriptive statistics to explain the social and demographic characteristics of the female head of household workers and the multiple regression test to analyze the factors that influence the work hours of women workers. The results show that the characteristics of women heads of household workers in East Java are 54 years old on average, divorced, low educated, working alone in the agricultural sector, and having 1-2 household members. Social and demographic factors that influence the flow of their working hours are age, business sector, occupation status, and household members.